First records of marine microturbellarians (Platyhelminthes: Rhabdocoela, Fecampiida and Prolecithophora) from Peru, with the description of a new species - Velásquez-Rodriguez, Karen; Reyes, Jhoe; Steenkiste, Niels Van; Severino, Ruperto; Brusa, Francisco (Zootaxa, 2023)
The marine microturbellarian diversity is scarcely known from the Pacific coastline of South America. The coastal margin of Peru is highly influenced by cold-water currents (Humboldt Current System). These cold-water currents play important roles in shaping the marine species diversity in this area. However, there are no previous records of marine microturbellarians for Peru. Here, we describe a new species of Rhabdocoela and report on five other species of marine microturbellarians for this country. Carcharodorhynchus giaae n. sp. (Kalyptorhynchia, Schizorhynchidae), can be identified based on the configuration of the proboscis lips and the male and female genital systems. The male copulatory organ lacks a cirrus, but has a funnel-like, curved stylet with three pairs of spines along it, which distinguishes this species from its congeners. The female system has a vagina with a sclerotized, heavily coiled structure — a feature not mentioned in any known species of the same genus. In addition, we describe noteworthy features for another rhabdocoel, Trigonostomum galapagoense (Dalytyphloplanida, Trigonostomidae). Finally, we provide new records for three rhabdocoel species (Alcha evelinae, Itaipusa divae, Utelga heinckei), one species of Fecampiida (Urastoma cyprinae), and an unidentified species of Prolecithophora.